PENERAPAN MODEL PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SD NEGERI 21 PEKANBARU - ', Jepri; ', Erlisnawati; ', Lazim. N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: : This study was based by the low learning outcomes IPS students, with an average grade 64.6. While the value of minimum completeness criteria (KKM) IPS is 70., Among students who totaled 35 people only 14 people who reach KKM students with classical completeness 40%. This study is a Classroom Action Research (CAR) conducted aims to improve learning outcomes IPS third grade students of SDN 21 Pekanbaru to implement cooperative learning model. Formulation of the problem: Is the implementation of cooperative learning model can improve learning outcomes IPS Elementary School third grade students 21 Pekanbaru. The research was conducted on March 10, 2015 until April 7, 2015 with 3 cycles.The subjects were third grade students of SDN 21 Pekanbaru, amounting to 35 people were used as a source of data. Data collection instruments in this thesis is the teacher and student activity sheets and learning outcomes. This thesis presents the results obtained from the value of learning daily tests before the procedure with an average 64.6, an increase in the first cycle with the average being 71.7.In the second cycle increased by an average of 76.7 and an increase in cycle III with an average of 83.4. The activities of teachers in the learning process in the first cycle of the first meeting and the second meeting of the 66.7% increase to 79.2%. Cycle II first meeting and the second meeting 83.3% increase to 87.5%. In the third cycle of the first meeting and the second meeting 91.7% increase to 95.8%.Results of the data analysis activities of students in the first cycle the first meeting with an average of 62.5% and the second meeting increased to 75%. Cycle II first meeting and the second meeting 79.2% increase to 83.3%. In the third cycle of the first meeting and the second meeting 91.7% increase to 95.8%. Results of the study in class III SDN 21 Pekanbaru prove that the implementation of cooperative learning model can improve learning outcomes IPS third grade students of SDN 21 Pekanbaru. Keywords: Cooperative Learning Model, Learning Outcomes IPS.